Integrated Use of USLE, GIS, and Remote Sensing for Soil Erosion Mapping in Erbil Basin - Hemn Othman Salih; Dawod Rasooli Keya; Kamyar Mutalib Mohammed (Polytechnic Journal)
This article presents a comprehensive study on the integrated use of the Universal Soil Loss Equation (USLE), Geographic Information System (GIS), and remote sensing (RS) techniques for soil erosion mapping in the Erbil Basin. Soil erosion is a critical environmental issue that affects soil productivity, water quality, and ecosystem health. Understanding the spatial distribution and severity of soil erosion is essential for effective land management and erosion control measures. The study utilizes the USLE model, which considers multiple factors contributing to soil erosion, including rainfall erosivity, soil erodibility, slope length, slope steepness, and land cover. GIS tools were employed to process and analyze the spatial data, including digital elevation models (DEMs), soil maps, rainfall data, and land cover information. Remote sensing data from satellite imagery were incorporated to enhance the accuracy and spatial coverage of the soil erosion mapping. By integrating these approaches, a comprehensive soil erosion map of the Erbil Basin was generated, providing insights into the extent and severity of erosion across the study area. The results depicted variations in soil erosion rates, identifying high-risk areas prone to erosion and highlighting the factors contributing to erosion vulnerability. The estimated yearly soil loss in the context of USLE was ranged from 1.9 to 6.3 ton per hectare.